Marketing analysis of the technological equipment market for the Russian logging industry - Yu. V. Astashova; I. Yu. Okolnishnikova; O. N. Gatilova (Вестник университета)
The results of the analysis of the equipment market for the logging industry in Russia are presented. A literary review of the domestic and foreign equipment markets is presented, the size of the market is estimated, its segmentation is carried out, consumer preferences are identified and characterized. The assessment of the key product range for the industry is carried out, the main foreign competitors are identified and the existing barriers to the entry of domestic products into the market are analysed, as well as ways to overcome them are proposed and justified. The features of the demand for products are analysed, the possibilities of import substitution of currently used logging machines are studied and the ways of their marketing promotion are presented. The directions of further development of forest engineering and the entire forest complex of Russia based on import substitution and ensuring the economic and technological security of Russia are substantiated.